PENENTUAN SKALA USAHA DAN ANALISIS EFISIENSI EKONOMI USAHATANI KOPI RAKYAT DI KABUPATEN ACEH TENGAH - Indra Indra (Jurnal Agrisep, 2011)
Economic scale and economic efficiency of coffee farm at Central Aceh DistrictABSTRACT. The aim of the research is to analyze some production factors that influence production of coffee, optimization level of using production factors (economic efficiency), and break even point of farm size (economic scale) on coffee farm in Central Aceh District. This research used survey method. Its population was coffee farmers in Central Aceh District. Sampling technique used was two stages cluster random sampling. The number of sample was 96 farmers that were consisted of 31 farmers from Kota Sub-District and 65 farmers from Timang Gajah Sub-District. The results of the research are: (1) man labor, fertilizer, plant area, number of tress, age of commodity, and farmers experience on cultivating coffee influence simultaneously and significantly on coffee production, (2) the use of those production factors on coffee farm in Central Aceh District was not efficient yet, (3) Average farm size was above break even point of farm size.